Resolução de conflitos ambientais: o espaço do consenso, do inegociável e do controle judicial - Moreira, Rafael Martins Costa (2020)
This thesis focuses on the issue of environmental dispute resolution and aims to establish legal criteria to demarcate the space of consensus and freedom of the parties, delimit the area of non-negotiable and the place of judicial intervention in disputes and agreements in environmental law. Initially, the question is whether the evolution of the civil process and means of dispute resolution has followed the complexity and dynamism of contemporary environmental and climate conflicts. Next, it is reflected on the emergence of new environmental legal conflicts, with the recognition of new values and new entitlements, in favor of future generations and the non-human environment, provided by the emergence and maturation of the environmental movement and the progressive relativization of legal anthropocentrism. To narrow the scope of the thesis, a concept of environmental legal conflict is proposed and its heterogeneity is recognized, indicating the need to find adequate solution formulas to the characteristics of the dispute. Two paradigms that guide the resolution of environmental conflicts are also categorized: the adversarial paradigm and the maximization of individual interests, and the paradigm of cooperativity and sustainability. Given the evolution of consensual mechanisms for resolving environmental disputes, since the environmental mediation movement in the United States and the use of the conduct adjustment term in Brazil, the possibilities and limits of these negotiationg formulas are analyzed. After recognizing the role of collaborative means as essential for providing prevention and adequate resolution of environmental conflicts, criteria are proposed to establish the non-negotiable space in these disputes. Finally, the thesis is dedicated to demarcating the area of jurisdictional intervention in environmental agreements. In conclusion, the thesis reflects on the hypothesis of the insufficiency of traditional mechanisms for resolving environmental disputes, since the Law does not yet respond to or keep pace with changes resulting from environmental and climate crises. It also considers the development of suitable methods of conflict resolution as a central point to enable the prevention of disputes and environmental damages, with priority for collaborative and consensual strategies, as long as the space of the legally non-negotiable is observed, subject to judicial control. It was opted for deductive, historical, comparative, case study, typological, bibliographic-investigative, jurisprudential research and topic-systematic interpretation methods